Association of perioperative fentanyl analog exposure with risk of psychiatric disorder in non-cardiac surgery: A 10-year retrospective study in a Korean tertiary hospital - Dong Yun Lee; Ah Ran Oh; Rae Woong Park; Jungchan Park (PLoS ONE, 2025)
Study objective To evaluate the risk of developing psychiatric disorders within three years after non-cardiac surgery in patients exposed to fentanyl analogs versus other opioids. Design Retrospective observational study. Setting Postoperative period. Patients The study included 52,640adult patients who underwent non-cardiac surgery at Samsung Medical Center, Seoul, Korea, between January 2011 and June 2019. Interventions Patients were divided into those exposed to fentanyl analogs and those exposed to other opioids. Propensity score matching and Cox regression analysis were used to compare the incidence of psychiatric disorders between the groups. Measurements Psychiatric outcomes, including depression, anxiety, stress-related disorders, substance use disorders, and psychotic disorders, were assessed. Main results The study included 52,640 patients, evenly split between the fentanyl and other opioid groups. Fentanyl exposure was associated with a higher incidence of composite psychiatric outcomes (hazard ratio [HR] 1.28 [1.13–1.46]; P < 0.001), including depression (HR 1.25 [1.08–1.45]; P = 0.003) and stress-related disorders (HR 1.45 [1.02–2.04]; P = 0.036). Subgroup analyses indicated increased risks in males, females, patients without alcohol history, and those not undergoing emergency surgeries. Conclusions Perioperative fentanyl use is linked to a higher risk of psychiatric disorders compared to other opioids. These findings emphasize the need for careful use and monitoring of fentanyl in surgical patients, considering both immediate and long-term mental health effects.